TreeTool: A tool for detecting trees and estimating their DBH using forest point clouds - Omar Montoya (Elsevier, 2021)
Trees’ inventory is an essential task in ecological assessment efforts in the fight against climate change. The diameter at breast height (DBH) of a tree is critical in forest inventory, particularly in estimating carbon content. This document presents TreeTool, a software tool written in Python to detect trees and measure their DBH from forest dense point clouds. The software performed acceptably against others in completeness, accuracy, location error, and diameter error benchmarks.